(untitled) (Journal of Health, Population and Nutrition, 2011)
The objective of the study was to evaluate the performance of nitrate reductase assay (NRA) as a rapid, reliable and inexpensive method for drug-susceptibility testing (DST) of Mycobacterium tuberculosis against firstline antitubercular drugs, such as rifampicin (RIF), isoniazid (INH), streptomycin (STR), and ethambutol (EMB). In total, 286 isolates were subjected to test by proportion method (PM) and NRA. By comparing the results of NRA with those of the gold standard PM, sensitivities and specificities were 98.4%, 97%, 88.5%, and 94.2% and 100%, 100%, 94%, and 99% for RIF, INH, STR, and EMB respectively. The positive predictive values were 100%, 100%, 95%, and 98% for RIF, INH, STR, and EMB respectively. The negative values were 99%, 98%, 87%, and 96% for RIF, INH, STR, and EMB respectively. The median time of obtaining results was shorter using NRA (10 days) compared to PM (28 days). An excellent agreement was observed between the two phenotypic tests with the κ values of 0.98, 0.97, 0.81, and 0.93 for RIF, INH, STR, and EMB respectively. The results demonstrated that NRA is suitable for the early determination of INH and RIF resistance and has the potential to be a useful tool for rapid drug-sensitivity test of M. tuberculosis in resource-constrained settings. Key words: Antitubercular agents; Mycobacterium tuberculosis; Drug resistance, Mutiple; Nitrate reductase assay; Tuberculosis, Multi-drug-resistant; India DOI: 10.3329/jhpn.v29i1.7563 J HEALTH POPUL NUTR 2011 Feb;29(1):20-25